Dampak Program Z-Mart Kalteng Berkah Terhadap Peningkatan Ekonomi Mustahik Di Kota Palangka Raya - Muhammad Rifqi; Zulkifli; Muhammad Noor Sayuti; Itsla Yunisva Aviva (Program Studi Ekonomi Syariah IAIN Parepare, 2026)
The presence of modern retail stores in Central Kalimantan has intensified competition for micro-enterprises, reducing their competitiveness and limiting access to capital. This study examines the impact of the Z-Mart Kalteng Berkah Program on improving the economic conditions of mustahik in Palangka Raya City and evaluates its empowerment effectiveness. A descriptive qualitative approach was employed through field research, with primary data collected from in-depth interviews involving four key informants, including BAZNAS program managers, field facilitators, and beneficiaries. The findings reveal that the program significantly increased beneficiaries' daily income from approximately IDR 200,000–300,000 to IDR 400,000–500,000. Support in the form of display shelves and retail banners enhanced the competitiveness of small shops, while mentoring improved financial management literacy and economic independence. Nevertheless, more comprehensive market analysis is needed to reduce unsold inventory (dead stock), accompanied by continuous mentoring. Overall, the Z-Mart Kalteng Berkah Program represents an effective productive zakat empowerment model by integrating business capital assistance with capacity building.